(untitled) (Journal of Engineering, 2020)
This study investigates the results of electrocoagulation (EC) using aluminum (Al) electrodes as anode and stainless steel (grade 316) as a cathode for removing silica, calcium, and magnesium ions from simulated cooling tower blowdown waters. The simulated water contains (50 mg/l silica, 508 mg/l calcium, and 292 mg/l magnesium). The influence of different experimental parameters, such as current density (0.5, 1, and 2 mA/cm2), initial pH(5,7, and 10), the temperature of the simulated solution(250C and 35 0C), and electrolysis time was studied. The highest removal efficiency of 80.183%, 99.21%, and 98.06% for calcium, silica, and magnesium ions, respectively, were obtained at a current density of 1 mA/cm2, initial PH=7, the temperature of 250C and treatment time 60 min. The results have shown the ability of the EC process to remove silica and hardness ions from CTB water.